Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

A voice from the South - Cooper, Anna Julia (University of North Carolina at Chapel Hill Library, 2017)
The first book by Anna J. Cooper, A Voice From the South, presents strong ideals supporting racial and gender equality as well as economic progress. It’s a forward-thinking narrative that highlights many disparities hindering the African American community. Anna J. Cooper was an accomplished educator who used her influence to encourage and elevate African Americans. With A Voice From the South, she delivers a poignant analysis of the country’s affairs as they relate to Black people, specifically Black women. She stresses the importance of education, which she sees as a great equalizer. Cooper considers it a necessary investment in not only the individual but the community. She also criticizes the depictions of African Americans in literature by some of the day’s most popular authors. She calls for more realistic portrayals that are both honest yet positive. Cooper provides an unflinching critique of mainstream America as it relates to the Black population. A Voice From the South broaches pivotal topics such as women’s rights, segregation and the need for higher education. With an eye-catching new cover, and professionally typeset manuscript, this edition of A Voice From the South is both modern and readable.
Première publication 1892 https://docsouth.unc.edu/church/cooper/cooper.html
Keywords: 1800-1899; afro-féminisme; amériques; approches et analyses; capitalisme; droits des femmes*; féminismes noirs; histoire et politique; militance; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; éducation; états-unis

Blues et féminisme noir - Davis, Angela (Libertalia, 2017)
Blues et féminisme noir explore l’œuvre de deux blueswomen quelque peu oubliées : Gertrude « Ma » Rainey (1886-1939) et Bessie Smith (1894-1937). La première incarne le blues traditionnel, la seconde, le blues classique. Dévalorisée par les spécialistes du blues et du jazz – qui sont en général des hommes blancs –, l’œuvre de ces chanteuses porte un message spécifique : elle affirme la place et les revendications d’autonomie des femmes noires américaines. En analysant et en contextualisant les paroles de leurs chansons, Davis met en évidence les prémices du féminisme noir et les signes avant-coureurs des grandes luttes émancipatrices à venir. Elle montre que Ma Rainey et Bessie Smith furent les premières rock stars de l’histoire de la musique : or elles étaient noires, bisexuelles, fêtardes, indépendantes et bagarreuses. Elles posèrent les bases d’une culture musicale qui prône une sexualité féminine libre et assumée, qui appelle à l’indépendance et à l’autonomie des femmes aux lendemains de la période esclavagiste, en revendiquant avec détermination l’égalité de « race » et de genre. Cette réflexion s’étire aux années 1940 en évoquant l’œuvre de Billie Holiday (1915-1959). Angela Davis réhabilite la conscience sociale de cette chanteuse d’envergure, trop souvent présentée sous le simple prisme des turpitudes de sa biographie. Blues et féminisme noir propose une histoire féministe et politique de la musique noire des années 1920 aux années 1940.
Keywords: 1900-1999; 1920-1929; 1930-1939; 1940-1949; DIG; afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; féminismes noirs; histoire; inégalités; militance; musique; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis; études culturelles

De la marge au centre : théorie féministe - hooks, bell (Cambourakis, 2017)
Avec "De la marge au centre", son deuxième essai paru aux États-Unis en 1984, bell hooks poursuit la réflexion initiée dans "Ne suis-je pas une femme?" Étudiant les succès et les manquements des mouvements féministes qui ont traversé le xxe siècle, elle constate l'échec de la création d'un féminisme de masse qui s'adresserait à toutes. Elle s'attache ainsi, dans un style toujours accessible, à bouleverser les représentations habituelles de la pensée féministe majoritaire en plaçant au centre de sa réflexion les femmes noires et/ou des milieux populaires, insistant sur le besoin profond d'une approche révolutionnaire de ces questionnements. Cet ouvrage percutant a imposé bell hooks comme l'une des voix les plus influentes et stimulantes de la scène féministe.
Traduction de : Feminist theory : from margin to center. Première édition 1984. Donné au lire dans la cours POL4212: p. 107-118 **Trigger warning: Insulte raciste à la p. 116.
Keywords: 1900-1999; EDI; afro-féminisme; amériques; approches et analyses; black feminism; classe sociale; com5170; cours; discours dominant; fem1000; femmes* noires; féminismes noirs; histoire du féminisme; incontournable; justice sociale; militance; mouvements féministes; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; sex3383; sexisme; systèmes d'oppressions; thématiques; théorie féministe; états-unis

Radical reproductive justice: Foundation, theory, practice - Ross, Loretta; Roberts, Lynn; Derkas, Erika; Peoples, Whitney; Bridgewater Toure, Pamela (Feminist press, 2017)
Expanding the social justice discourse surrounding "reproductive rights" to include issues of environmental justice, incarceration, poverty, disability, and more, this crucial anthology explores the practical applications for activist thought migrating from the community into the academy. Radical Reproductive Justice assembles two decades’ of work initiated by SisterSong Women of Color Health Collective, creators of the human rights-based “reproductive justice” framework to move beyond polarized pro-choice/pro-life debates. Rooted in Black feminism and built on intersecting identities, this revolutionary framework asserts a woman's right to have children, to not have children, and to parent and provide for the children they have.
Keywords: afro-féminisme; approches et analyses; discipline; droit; droits des femmes*; intersectionnalité; justice reproductive; justice sociale; maternité; militance; santé; science politique et droit; sciences humaines; sociologie; thématiques